Implementation of the Project Based Learning (PjBL) Model to Students’ Problem Solving Ability and Entrepreneurial Interest in Environmental Change Material - Nana Kariada Tri Martuti; Zulfatul Aliyah (Universitas Negeri Semarang, 2024)
Problem-solving ability and entrepreneurial interest are the kinds of skills that must be owned by the students to face the world of work and citizenship in the 21st century. The PjBL model through waste product development projects as a solution to solving environmental problems is considered a potential learning strategy for developing problem-solving ability and entrepreneurial interest student. The background of SMA Negeri 1 Kersana as an adiwiyata school which has various waste management and processing activities has the potential to implement projects to manage old leaf waste into leaf skeleton craft products. This research aims to analyze the effectiveness of the PjBL model on students' problem-solving ability and entrepreneurial interest in environmental change material, and analyze the relationship between problem-solving ability and entrepreneurial interest in learning the PjBL model. This research used pre experimental design with the one shot case study. The population in this study were class X students of SMA Negeri 1 Kersana who received biology subjects for the 2023/2024 school year. Sampling was carried out using cluster random sampling technique, the sample in this study was class X-2 with 36 students. The test instruments was used to measure students' problem solving ability while questionnaire instruments was used to measure entrepreneurial interest. The average score of problem solving ability was 77.05 and the posttest classical completeness of problem solving ability was 91.67%. The average score ofentrepreneurial interest was 83.9 and the criteria level for entrepreneurial interest is good at 27.78%, very good at 72.22%. Based on these results, it can be concluded that PjBL is effective on students' problem-solving ability and entrepreneurial interest in environmental change material. The results of a simple linear regression test between problem solving ability and students' entrepreneurial interest show tcount > ttable, namely 2.466 > 2.032 and a significance level of 0.019 < 0.05, so there is a significant positive relationship between problem solving ability and students' entrepreneurial interest in the PjBL learning model.